Optimizing the Potential of Underachiever Students Through WDEP Engineering Reality Counseling - Dian Melady; Syaifatul Jannah (Penerbit Presisi Pustaka, 2026)
This study is motivated by the presence of students who show underachiever behavior, namely conditions where students have good academic potential but are unable to achieve optimal performance. This phenomenon becomes an important concern in guidance and counseling services because it affects students' academic and psychological development. This study aims to describe the application of reality counseling in dealing with underachiever students and to identify behavioral changes after counseling services are provided. This research uses a qualitative descriptive approach. Data were collected through observation, interviews, and documentation. The subjects were underachiever students and guidance and counseling teachers. Data analysis was conducted through data reduction, data display, and conclusion drawing using triangulation techniques to ensure data validity. The results show that the application of reality counseling using WDEP (Want, Doing, Evaluation, Planning) techniques helps students understand their needs, evaluate their behavior, and plan more responsible actions. The changes include increased learning motivation, discipline, and student engagement in academic activities. Thus, reality counseling is effective as a strategy in handling underachiever students.